Burkitt Lymphoma of Thyroid Gland in an Adolescent - K. Cooper; A. Gangadharan; R. S. Arora; R. Shukla; B. Pizer (Case Reports in Pediatrics)
Burkitt Lymphoma is a highly aggressive form of non-Hodgkin’s lymphoma that in nonendemic areas has abdominal primary sites. We report a very rare case of Burkitt lymphoma of the thyroid gland presenting as a rapidly growing thyroid swelling in a 14-year-old white Caucasian British male with no preexisting thyroid or medical problems. The diagnosis was confirmed by an open wedge biopsy following a fine needle aspiration. The patient was treated according to the Children’s Cancer and Leukaemia Group guidelines for BL—Group B protocol and currently is in remission.